The Impact of Corporate Governance in Forming a Strong Supply Chain: Evidence from Indonesia - Giyanto Giyanto; Indrianawati Usman; M Jihadi; Titik Ambarwati; Asrini Asrini; Musnaini Musnaini (International Journal of Supply Chain Management, 2020)
The main purpose of the recent research is to investigate the importance of corporate governance in evaluating supply chain capabilities. This investigation aims to assess the direct effect of SC information systems potential, SC relational potential and CG on the SC command and control efficiency of manufacturing companies operational in Tin sector of Indonesia. Additionally, we have investigated the balancing effect of CG in the collaboration between SC capability and operating efficiency of the supply chain. The scholars have utilized the SEM-PLS technique to accomplish the distinctive targets of recent research. The observations of the recent research supported the suggested findings. The research demonstrates that the organization’s strategy to customer expectations is also associated with the manufacturing-oriented approach. The implications of the report may help decision-makers identify the problems associated with the administration of the corporate governance supply chain. It is one of the few pioneering researches on these problems as per researcher’s knowledge.